1998
DOI: 10.1001/jama.280.2.140
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Excessive Weight Gain With Intensive Therapy of Type 1 Diabetes on Lipid Levels and Blood Pressure

Abstract: Context.-Intensive treatment of type 1 diabetes results in greater weight gain than conventional treatment. Objective.-To determine the effect of this weight gain on lipid levels and blood pressure. Design.-Randomized controlled trial; ancillary study of the Diabetes Control and Complications Trial (DCCT). Setting.-Twenty-one clinical centers. Participants.-The 1168 subjects enrolled in DCCT with type 1 diabetes who were aged 18 years or older at baseline. Intervention.-Randomized to receive either intensive (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
347
3
11

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 418 publications
(375 citation statements)
references
References 21 publications
14
347
3
11
Order By: Relevance
“…The study also confirms that, as is the case in nondiabetic subjects, most E2/2 subjects have low lipids, and that only with a second hit, such as the weight gain with intensive diabetes therapy [32], which occurred in the one hyperlipidemic E2/2 subject, that the effect of the e2 allele is manifested as hyperlipidemia and remnant removal disease. The study also demonstrates that the frequency of apo E2 homozygosity in these Type 1 diabetic subjects is similar to that of the normal population (0.7% versus 0.8%, respectively).…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…The study also confirms that, as is the case in nondiabetic subjects, most E2/2 subjects have low lipids, and that only with a second hit, such as the weight gain with intensive diabetes therapy [32], which occurred in the one hyperlipidemic E2/2 subject, that the effect of the e2 allele is manifested as hyperlipidemia and remnant removal disease. The study also demonstrates that the frequency of apo E2 homozygosity in these Type 1 diabetic subjects is similar to that of the normal population (0.7% versus 0.8%, respectively).…”
Section: Resultssupporting
confidence: 77%
“…It confirms that only with a second hit, such as the weight gain with intensive diabetes therapy [32] that occurred in the one hyperlipidemic E2/2 subject, that the effect of the e2 allele is manifested as hyperlipidemia and severe remnant removal disease.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…This has been demonstrated in large-scale studies [9,10]. Excessive weight gain has been identified as a major concern with long-term intensive therapy of Type 1 diabetes mellitus [26]. In this trial, a significantly lower mean body weight was observed in the insulin detemir/insulin aspart group than in the NPH/regular human insulin group after 18 weeks of treatment.…”
Section: Discussionmentioning
confidence: 54%
“…This, in turn, may impair treatment adherence and impede therapy intensification, with consequent failure to achieve glycaemic goals 1, 2. Weight gain is associated with an increased risk of coronary heart and cardiovascular disease in people with diabetes 3, 4, a troubling prospect given that 80–90% of people with T2D are already overweight before insulin replacement 5. Landmark trials, notably the UK Prospective Diabetes Study 6 and the Diabetes Control and Complications Trial 7, showed that the cost of improved glycaemic control was considerable weight gain with intensive treatment regimens.…”
Section: Introductionmentioning
confidence: 99%